2022
DOI: 10.1021/acsomega.2c01497
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Molecular Modeling Studies of a Novel Benzimidazole as an Aromatase Inhibitor

Abstract: In this study, a series of novel 1,3,4-oxadiazole-benzimidazole derivatives were designed and synthesized. Their cytotoxic activities against five cancer cell lines, including A549, MCF-7, C6, HepG2, and HeLa, were evaluated by the MTT assay. The compounds 5b , c showed satisfactory potencies with much higher anticancer activity in comparison to the reference drug doxorubicin against the studied cancer cell lines. In vitro , enzymatic inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The Aromatase Substrate undergoes rapid photobleaching in aqueous solutions 32 . In our experience, the linear phase begins in the kinetic mode for 60 mins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Aromatase Substrate undergoes rapid photobleaching in aqueous solutions 32 . In our experience, the linear phase begins in the kinetic mode for 60 mins.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro Aromatase enzymatic assay ability of the test compound (ziprasidone) to inhibit aromatase enzyme was performed using a aromatase Inhibitor Screening Kit (Catalog #K984-100; Store at -20°C) which is a high-throughput uorescence-based assay kit enables reliable, rapid, characterization of drugs and other small molecules for compound-aromatase interaction with human aromatase 32 . The experimental protocol was followed according to the user manual.…”
Section: Annexin V/pi Assay Formentioning
confidence: 99%
“…Additionally, molecular docking studies were conducted to detect their binding sites and types of interactions with aromatases. Compounds ( 130 ) and ( 131 ) were also investigated via molecular dynamic simulations for its possible binding mode to CYP19A1 and it was found that both derivatives had great potential as compared to others [ 124 ].…”
Section: Miscellaneous Anticancer Properties Of 134-oxadiazole Deriva...mentioning
confidence: 99%
“…One of the principal strategies for drug discovery of new drug candidates is to amalgamate two or more pharmacophoric moieties in a single molecule to achieve the synergistic effect or obtain anticancer agents via a novel mechanism of action. In light of the afore-mentioned facts and continuation of our previous studies on identifying new antiproliferative activities, 16,23–26 hybrid compounds containing a 1,2,4-triazole ring and a hydrazone moiety were synthesized by employing an iodine mediated reaction in an attempt to get new effective anticancer molecules with increased potency (Fig. 3).…”
Section: Introductionmentioning
confidence: 99%